Amphiphilic oligopeptides grafted to PDMS‐based diblock copolymers for use in antifouling and fouling release coatings1. (30th April 2015) - Calabrese, David R.; Wenning, Brandon; Finlay, John A.; Callow, Maureen E.; Callow, James A.; Fischer, Daniel; Ober, Christopher K.; Domb, Abraham; Slomkowski, Stanislaw
<x xml:space="preserve">Abstract</x> Amphiphilic surfaces, having both hydrophobic and hydrophilic properties, have been considered for marine antifouling and fouling release applications, as they may provide an environmentally friendly non‐biocidal alternative for surface coating. Here, we report a new class of polymers modified with amphiphilic side chains constructed from non‐natural oligopeptides. These non‐natural amino acids have a diverse array of functionalities and polarities that can be arranged in any sequence to optimize antifouling and fouling release behavior. Because of advances in solid state peptide synthesis, these peptides can be prepared on a multiple gram scale in a short period of time. Different sequences of non‐natural amino acids were synthesized to determine the effect on the physical and antifouling properties of the surface. These oligopeptide sequences were attached to a PS‐b‐P(DMS‐stat‐MVS) diblock copolymer using thiol‐ene "click" chemistry. The modified polymers were spray coated onto treated glass slides and characterized using water bubble contact angle measurements and near‐edge X‐ray absorption fine structure. The coatings were tested for antifouling and fouling release performance against spores and sporelings (young plants), respectively, of the green seaweed (alga) Ulva linza and also for non‐specific protein absorption. Copyright © 2015 John Wiley & Sons, Ltd.